Design intent for hazard and operability studies. Issue 1 (18th October 2014) - Baybutt, Paul
Abstract : The Hazard and Operability (HAZOP) Study undoubtedly is the most commonly used process hazard analysis method in the world today. It is based on considering deviations from the design intent for a process to identify hazard and operability scenarios. Often, HAZOP Study practitioners generate deviations using a short checklist of process parameters. This practice likely results in missed scenarios. A full consideration of design intent is needed to ensure that scenarios are identified as completely as possible. This situation probably arises because of a lack of understanding of the HAZOP Study and the scope of design intent. This article describes the meaning and use of design intent to encourage HAZOP Study practitioners to address it fully during studies. © 2015 American Institute of Chemical Engineers Process Saf Prog 35: 36–40, 2016